Study of tumor-associated macrophages in triple-negative breast cancer and their correlation with clinicopathological parameters - Priyalatha Kurusamy (2014)
Triple-Negative Breast Cancer (TNBC) is defined by the lack of immunohistochemical expression in both estrogen and progesterone receptors as well as lack of HER-2 gene amplification. Due to the lack of targetable molecules, limited treatment options are available, prompting the need to identify prognostic factors for TNBC patients. Evidence suggests that Tumor Associated Macrophages (TAMs) found in breast cancers can contribute in tumorigenesis via angiogenesis and inhibition of immune response. The expression levels of TAMs in both stromal (CD68S) and tumor nest (CD68T) regions were evaluated by performing immunohistochemistry using CD68 biomarker in tissue microarrays with tumors from 183 TNBC cancer cases. Correlations for CD68 expression with various clinicopathological parameters was determined using Pearson’s Correlation Test and survival outcomes were estimated using Kaplan Meier analysis. Results showed that (a) CD68S expression significantly correlated with tubule formation (P=0.021), growth pattern (P=0.026) and histological grade (P=0.004) and (b) CD68T expression significantly correlated with mean age (P=0.016), growth pattern (P=0.003), associated DCIS (P=0.004) and lymphovascular invasion (P=0.004). There was also significant association for CD68T expression with disease free survival (P=0.021). The results obtained in this study convey that TAMs have potential to be considered as prognostic markers in TNBC.